TRATEGIC MANAGEMENT In the FUNCTION of SPORT And RECREATIONS - Dejan Gligović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In countries throughout holy, sport, recreation and plays promotes the health, spirit and the tenement. They us learns important lessons from the life about the respect, leadership and controls. They promote the equality for all and remove differences among men. Modern society now takes over the power and possibilities which has the sport, recreation and plays, carrying out him in programmes its national governments throughout holy. In this way, develops partnerships with all sectors and all levels of company, from governments, over holy sport to the civil society in all his diversity, in order to affirms value which breeds sport would not perform boys and girls on sports courts and sports grounds those would teach the Deco and their families about benefits of physical activities. In order to would come about like this ambitious and the significant project indispensable precondition is the strategic planning of development of sport on the specified area and in which has been joined in top-grade managers from different domains. Special attentions must dedicate execution is adopted strategies, because if is absent the direct application is adopted strategies, the per se selected strategy not did introduce herself the no progress.